Non-invasive Imaging and Tracking of Engineered Human Muscle Precursor Cells for Skeletal Muscle Tissue Engineering Using Positron Emission Tomography - Haralampieva, Deana (J Nucl Med, 2016)
Transplantation of human muscle precursor cells (hMPCs) is envisioned for the treatment of various muscle diseases. However, a feasible non-invasive tool to monitor cell survival, migration and integration into the host tissue is still missing. METHODS: In this study, we designed an adenoviral delivery system to genetically modify hMPCs to express a signaling-deficient form of a human dopamine D2 receptor (hD2R). The gene expression levels of the receptor were evaluated by Reverse Transcriptase Polymerase Chain Reaction (RTPCR) and infection efficiency was visualized by fluorescent microscopy. Viability, proliferation and differentiation capacity of the transduced cells were confirmed and their sustained myogenic phenotype was shown by flow cytometry analysis and fluorescent microscopy. 18F-Fallypride and 18F-FMISO, two well-established PET radioligands, were successfully synthesized and evaluated for their potential to image engineered hMPCs in a mouse model. Furthermore, biodistribution studies and autoradiography were also performed to determine the extent of signal specificity. RESULTS: To address the feasibility of the presented approach for tracking of hMPCs in an in vivo model, we first evaluated the safety of the adenoviral gene-delivery, which showed no detrimental effects on the primary human cells. Specific binding of 18F-Fallypride to hD2R_hMPCs was demonstrated in vitro, as well as in vivo, by performing autoradiography, biodistribution and PET experiments, respectively. Furthermore, 18F-FMISO uptake was evaluated at different time-points after cell inoculation in vivo, showing high signal only at the early stages. Finally, histological assessment of the harvested tissues confirmed the sustained survival of the transplanted cells at different time-points with formation of muscle tissue at the site of injection. CONCLUSION: We here propose a signaling-deficient human D2R as a potent reporter for in vivo hMPCs PET tracking by 18F-Fallypride. This approach is a significant step forward towards a potential non-invasive tracking of hMPC_hD2R cells and bioengineered muscle tissues in the clinic.